Minimum standards in the European Account Preservation Order - Golak, Mateusz Wiktor (Review of European and Comparative Law, 2019)
The article is devoted to minimum standards in the new procedural instrument - the European Account Preservation Order. The main purpose of the preservation proceeding is to grant an interim order of creditor’s claim on debtor assets, without overburdening his property. Due to the complicated procedure established by Regulation (EU) No 655/2014, the European Account Preservation Order should serve as an additional and optional measure for the creditor, the examination of the minimum standards is essential. The Author indicates the relation between above-mentioned regulation and other regulations and gives explanation why this instrument is another symptom of the new EU legislator's approach to cross-border civil matters. Since the debtor is a person whose interests are most affected by the preservation on the bank account, it is necessary to specify his rights and obligations in this proceedings.